Innovation team forming and the modification of its behaviour in an enterprise - Zabielavičienė, Irena (Business: Theory and Practice, 2008)
The present paper is concerned with forming of an innovation team and the modification of its behaviour in conformity with the main statements of organizational behaviour and management psychology. The drawn up logical scheme of forming an innovation team embraces the active processes of its formation, differentiation, integration and its mature stage as well as its correlation processes with the team’s effectiveness factors and the potential psychological problems. The problems of the inner compatibility of the individual members as well as their personal creativity, the stimuli for their private motivation and their impact on the general record are taken into account. The alternatives of the productivity increase means, taking into consideration the concord of the team and its rate, are also looked into. The analysis of the appropriate ways of thinking and the tolerance of indeterminate combinations are also dealt with. The desirable aspects of the ethical behaviour of the team members are analysed as well in the given paper. The aspects of the perception of the working environment and its impact on the records of the innovation team are fully considered. Side by side with the innovation team behaviour assessment, resulting from the functional analysis, the logical scheme and the behaviour modification stages of the team are presented.Article in Lithuanian. Inovacijų komandos formavimasis ir jos elgsenos modifikavimasSantrauka. Straipsnyje  nagrinėjama inovacijų komandos formavimasis ir jos elgsenos modifikavimas remiantis organizacinės elgsenos ir vadovavimo psichologijos teiginiais. Sudaryta  inovacijų  komandos  formavimosi  loginė  schema,  atspindinti  komandoje  vykstančius  procesus  jos  formavimo, diferenciacijos, integracijos ir brandos etapais, taip pat procesų sąsajas su komandos efektyvumo veiksniais ir potencialias psichologines problemas. Analizuojama  komandos  narių  suderinamumo  problemos  ir  kūrybingumo  vidinės  motyvacijos  dirgiklių  įtaka  jos  darnai. Nagrinėjamos darbo produktyvumo didinimo priemonių alternatyvos, atsižvelgiant į komandos darną ir jos normas. Pateikta inovacijų komandos vaidmenims tinkamų mąstymo būdo ir neapibrėžtumo tolerancijos derinių analizė. Nagrinėjami inovacijų komandos vaidmenims pageidaujamo moralinio elgesio analizės klausimai. Analizuojama darbo aplinkos suvokimo veiksniai ir jo įtaka inovacijų komandos charakteristikoms. Pateikta inovacijų komandos elgsenos įvertinimo, atliekant funkcinę analizę, loginė schema ir nagrinėjami elgsenos modifikavimo etapai.Reikšminiai žodžiai: inovacijos, komanda, elgsena, inovacijų vadyba, komandinis darbas.First published online: 22 Dec 2008